Allocation of Education Budget in Indonesia - Saputra, Agung (Budapest International Research and Critics University, 2018)
Education is considered to have a very important role in promoting the civilization of a nation. Good quality education can encourage the creation of a quality society, creative and productive until finally able to achieve welfare. Through this national education system, the government should be able to ensure equal distribution of educational opportunities, as well as the relevance and efficiency of education management to face challenges in line with the changing demands of local, national and global life. The budget allocation system for education in Indonesia is heavily influenced by government policies. Education financing depends on the management of educational institutions, but budget allocations used must conform to national financing standards. Education in Indonesia, implemented in accordance with educational policies that regulate the national education system, as well as the allocation of 20% education funding obtained from the state budget and APBD.